The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1093/humrep/deh060
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancies in Caesarean section scars: the 8 year experience of one medical centre

Abstract: The women at risk for pregnancy in a Caesarean section scar appear to be those with a history of placental pathology, ectopic pregnancy, multiple Caesarean sections and Caesarean breech delivery. Heightened awareness of this possibility and early diagnosis by means of transvaginal sonography can improve outcome and minimize the need for emergency extended surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
222
1
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(242 citation statements)
references
References 20 publications
4
222
1
13
Order By: Relevance
“…2 Although a series of 18 and eight CSP cases were reported by Jurkovic et al and Maymon et al, respectively, the majority of data on CSP are found in individual case reports or small case series. 4,11 To the best of the authors' knowledge, this is the first case series to exclusively present suction evacuation and methotrexate as a treatment modality; this will hopefully aid in the acceptance of this approach as an effective treatment option for CSP.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2 Although a series of 18 and eight CSP cases were reported by Jurkovic et al and Maymon et al, respectively, the majority of data on CSP are found in individual case reports or small case series. 4,11 To the best of the authors' knowledge, this is the first case series to exclusively present suction evacuation and methotrexate as a treatment modality; this will hopefully aid in the acceptance of this approach as an effective treatment option for CSP.…”
Section: Discussionmentioning
confidence: 87%
“…7 Maymon et al recommended a dual approach, combining transvaginal and transabdominal scans of the patient with a full bladder; the latter provides a 'panoramic' view of the uterus and an accurate measurement of the distance between the gestational sac and the bladder. 11 This technique was used to diagnose CSP in one patient in the current case series, as the patient's uterus was pulled up due to her four previous Caesarean surgeries. Another diagnostic method proposed by Jurkovic et al is the negative sliding organ sign, defined as the inability to displace the gestational sac from its position at the level of the internal cervical opening using gentle pressure applied with a transabdominal probe.…”
Section: Lscs = Lower Segment Caesarean Section; β-Hcg = β-Human Chormentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a cesarean scar pregnancy is thought to be considerably more forceful than placenta previa or accreta in light of the fact that it attacks the myometrium in the primary trimester. Patients who have experienced different cesarean segments give off an impression of being at expanded hazard for in-scar implantation of the ensuing pregnancy on account of expanded scar surface zone [4,8,9]. With the coming of transvaginal sonography and with the utilization of saline imbuement, it is conceivable to survey postcaesarean area uterine divider respectability even in the nonpregnant state [4,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Doppler imaging in recent years 16,17 . Cesarean scar pregnancy is diagnosed on patients having amenorrhea and a history of prior caesarean section.…”
mentioning
confidence: 99%